2019
DOI: 10.1103/physrevb.100.075123
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility and simulated neutron signal in the two-dimensional Hubbard model

Abstract: We compute dynamic spin susceptibilities in the two-dimensional Hubbard model using the method of Dual Fermions and provide comparison to lattice Monte Carlo and cluster dynamical mean field theory. We examine the energy dispersion identified by peaks in Imχ(ω, q) which define spin modes and compare the exchange scale and magnon dispersion to neutron experiments on the parent La2CuO4 cuprate. We present the evolution of the spin excitations as a function of Hubbard interaction strengths and doping and explore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
2
23
1
Order By: Relevance
“…We next examine the charge properties. Figure 5 [49,57]. We also note that the maximum energy of the charge excitation does not change much as U increases before the Mott gap is opened, while it increases rapidly as the gap is opened.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…We next examine the charge properties. Figure 5 [49,57]. We also note that the maximum energy of the charge excitation does not change much as U increases before the Mott gap is opened, while it increases rapidly as the gap is opened.…”
mentioning
confidence: 71%
“…DF is accurate at high temperature [46] but uncontrolled in practice in the sense that adding systematic corrections, while possible in theory [47,48], is not feasible for the parameters studied here. A detailed assessment of the approximation errors of the susceptibility and the single-particle properties on the square lattice [49] showed that while dopingand interaction dependent scaling effects were present, the overall momentum dependence was accurate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We note that recent theory work using dual fermion methods, cluster dynamical mean field theory, and quantum Monte Carlo have also see the gapped Y-shaped magnon spectrum (LeBlanc et al 2019). With the agreement between the analytical approaches of section 2.4 and cluster dynamical mean field theory for transport properties, it is worth examining the magnetic properties of the analytical models in future work.…”
Section: Antiferromagnetic Correlations In the Pseudogap Phasementioning
confidence: 79%